All Days 2010
DOI: 10.2118/128424-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alternative Initial Responses to Kicks Taken during Managed Pressure Drilling

Abstract: An industry-supported research project has completed its evaluation of alternative initial responses to kicks taken during the constant bottom hole pressure (CBHP) method of managed pressure drilling (MPD) operations. The evaluation is the first phase of a study that is intended to provide a basis for comprehensive, reliable well control procedures for MPD operations. The evaluation was based primarily on computer simulations of multiple alternative initial responses to several causes and severities of kicks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A non-return valve or float valve is installed in the bottomhole assembly; it allows only downward flow of drilling fluids, which is necessary if the well will be statically underbalanced. There are other optional tools that can complement CBHP operation to improve wellbore pressure management such as coriolis meters (flowmeter), continuous circulating systems (CCS), downhole deployment valves, back pressure pumps, surface multiphase separators, pressure while drilling tools (PWD), and hydraulic flow modeling (Malloy 2008;Rehm 2009;Davoudi 2009). …”
Section: Constant Bottom Hole Pressure (Cbhp) Methods Of Mpdmentioning
confidence: 99%
See 3 more Smart Citations
“…A non-return valve or float valve is installed in the bottomhole assembly; it allows only downward flow of drilling fluids, which is necessary if the well will be statically underbalanced. There are other optional tools that can complement CBHP operation to improve wellbore pressure management such as coriolis meters (flowmeter), continuous circulating systems (CCS), downhole deployment valves, back pressure pumps, surface multiphase separators, pressure while drilling tools (PWD), and hydraulic flow modeling (Malloy 2008;Rehm 2009;Davoudi 2009). …”
Section: Constant Bottom Hole Pressure (Cbhp) Methods Of Mpdmentioning
confidence: 99%
“…However, three initial responses were demonstrated to have a broad application to different kick scenarios: a rapid increase of casing pressure until flow out equals flow in, a simple shut in, and lastly, an adaptation of the MPD pump shut down schedule that allowed confirmation of low rate kicks using a choked flow check. In addition, he concluded that the best initial response depended on well conditions and the equipment that is being used (Davoudi 2009;Davoudi et al 2010).…”
Section: Initial Responses During Well Control Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Without agusisma@itk.ntnu.no of well control (blowout), loss of assets, and even loss of life. The implication of such undesirable conditions are not only environmental, but it also concerns worker's safety [2]. Therefore, monitoring and control are important issues in oil well drilling.…”
Section: A Process Descriptionmentioning
confidence: 99%